Seroprevalence of hepatitis E virus infection in blood donors from Piauí State, Northeast Brazil - João Paulo da Silva-Sampaio; Raniela Borges Sinimbu; Julia Trece Marques; Abilio Francisco de Oliveira Neto; Livia Melo Villar (Brazilian Journal of Infectious Diseases)
A retrospective and cross-sectional study was carried out on blood donors from Piauí State located at Northeastern Brazil to evaluate the prevalence of Hepatitis E Virus (HEV) infection. Serum samples were tested for anti-HEV IgG and IgM using electrochemiluminescence and HEV RNA was tested using real time PCR. A total of 890 individuals were included with median age of 33.4 years and most of them were male and lived at Mid-Northern region of the State. Prevalences of anti-HEV IgG and IgM were 1.35 % and 0.11 %, respectively. None HEV-RNA was detected. This study demonstrated low prevalence of HEV infection in blood donors in this region.